DIFFERENTIATION OF BOVINE AND PORCINE GELATINES USING LC-MS/MS AND CHEMOMETRICS - SALAMAH, NINA; ERWANTO, YUNY; MARTONO, SUDIBYO; MAULANA, IRFAN; ROHMAN, ABDUL (International Journal of Applied Pharmaceutics, 2019)
Objective: To differentiate porcine gelatin and bovine gelatins using specific peptide markers as determined by liquid chromatography-mass spectrometry tandem with mass spectrometry (LC-MS/MS) and classify both gelatins using retention time and m/z as variables in principal component analysis (PCA). Methods: Porcine and bovine gelatins were digested using trypsin enzyme and then subjected to LC-MS/MS analysis. The specific peptides were identified. The classification between porcine and bovine gelatins was carried out using chemometrics of PCA using retention times and mass to charge ratio (m/z) as variables. Results: PCA using singvariables retention times (tR) and m/z could successfully classify porcine gelatin and bovine gelatin based on score plots of first principle component (PC1) and second principle component (PC2). The loading plot analysis showed that variable of tR32 and m/z32 contributed for the separation of both gelatins. Conclusion: The chromatograms of LC-MS/MS combined with PCA offered reliable method for differentiation between porcine and bovine gelatins. The developed method could be extended for halal authentication of food and pharmaceutical products via detection of porcine gelatin, non-halal gelatin.